2004
DOI: 10.1136/emj.2003.010165
|View full text |Cite
|
Sign up to set email alerts
|

Randomised, controlled outcome study of active mobilisation compared with collar therapy for whiplash injury

Abstract: Objectives: Standard therapy in Germany for acute whiplash injury has traditionally included a soft collar (cervical orthosis), an approach that is passive compared with early exercise and mobilisation. The purpose of this study is to examine the recovery in the first six weeks of groups of acute whiplash injury patients subjected to two different treatment approaches, the traditional approach of a collar compared with active, early mobilisation. Methods: Between August 1997 and February 2000 a randomised clin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
46
0
6

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(54 citation statements)
references
References 21 publications
2
46
0
6
Order By: Relevance
“…No additional studies were found through hand-searching reference lists and the tables of contents of selected journals or through contact with experts. Of the eight studies selected for inclusion, [15][16][17][18][19][20][21][22] only three were stand-alone studies. 15,16,22 Two of the remaining five constituted a pair, in which one study 21 was a follow-up to the other.…”
Section: Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…No additional studies were found through hand-searching reference lists and the tables of contents of selected journals or through contact with experts. Of the eight studies selected for inclusion, [15][16][17][18][19][20][21][22] only three were stand-alone studies. 15,16,22 Two of the remaining five constituted a pair, in which one study 21 was a follow-up to the other.…”
Section: Search Resultsmentioning
confidence: 99%
“…15,16,22 Two of the remaining five constituted a pair, in which one study 21 was a follow-up to the other. 20 The three remaining studies constituted a triplet in which two of the studies 18,19 were follow-ups to the first. 17 Methods, study population, interventions, and outcome measures used in the included studies are presented in Table 2, while the methodological quality assessment of the included studies is presented in Table 3.…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Yapılan çalış-malarda aktif hareketlerin whiplash yaralanmalı hastalarda boyunluk ve istirahat önerilen hastalardan daha fazla ağrıyı azalttığı gösterilmiştir (22)(23)(24). Fizik tedavi ile birlikte aktif egzersizlerin travmadan sonraki ilk 14 gün içinde uygulandığı hastalarda iyileşmenin erken ve geç dönemde devam ettiği gözlenmiştir (25 …”
Section: Mobilite Egzersizleriunclassified